Dampak Jumlah Kunjungan Wisatawan Nusantara terhadap Pendapatan Asli Daerah Kota Bogor - Anggraini, Asterina; Firman Syah; Ratri Kurniasari (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2024)
The tourism sector is a sector that has the potential to be developed as a source of regional income. As one of the sources of income, tourism is influenced by the number of tourists. The progress of the tourism sector in an area is highly dependent on the number of tourists who visit. The number of tourists will bring income to the area they visit. This study aims to determine the influence of the number of domestic tourist visits on the original income of Bogor City. This study uses a quantitative approach with a simple linear regression analysis method. The result of the study is that the number of domestic tourist visits has a significant positive influence on the PAD of Bogor City. The number of domestic tourist visits has a significant influence of 87% on the PAD of Bogor City. One of the government effort is to expand tourism activities such as entertainment, sports, camps, and competitions to increase the number of tourist visits so that it will increase the PAD of Bogor City.